Findings on the Chiropteran Status in Rautahat and Sarlahi, Nepal - Jha, Sunny Kumar (The Initiation, 2014)
Bats are the second most diverse mammals found in earth with around 1250 species in a single Chiropteran order. In Nepal, authentic list of 53 bat species have been prepared so far. This research was conducted in 10 VDCs of Rautahat and Sarlahi with the main objectives being assessing the status, diversity and threats. Key-informant survey, direct observation, roost survey and mist netting were done for assessing the primary data. A total of five species were identified. Deforestation, poaching, destruction of old houses, concrete constructions, use of chemical fertilizers in agricultural and fruit lands, change in the agricultural pattern and deliberate killing were identified as major. People’s attitude was satisfactory, though awareness level was found to be low. Diversity was found to be very high, but the respondents argued that the bats’ frequency was in continuous decrease from past few years. DOI: http://dx.doi.org/10.3126/init.v5i0.10253 The Initiation 2013 Vol.5; 50-54